2004
DOI: 10.1002/j.1556-6678.2004.tb00316.x
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Basic Counseling Skills With Children

Abstract: Counseling with children can be challenging for counselors whose training focused on adult clients. The purpose of this article is to offer information to counselors seeking to improve their skills with children, revisiting a topic discussed in an earlier Journal of Counseling & Development article by P. Erdman and R. Lampe (1996). Examples of microskills from actual counseling sessions and descriptions of stages and themes in the counseling process enhance understanding of child counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Professional preparation of counselors often centers on the needs of adults, but many counselors work with children (Velsor, 2004). The unique challenges, problems, stresses, and worries that children and families with mental health needs face are often read by counselors in a variety of settings (e.g., schools, community agencies, juvenile justice systems, child welfare programs, rehabilitation centers).…”
Section: Counselors and Children's Mental Healthmentioning
confidence: 99%
“…Professional preparation of counselors often centers on the needs of adults, but many counselors work with children (Velsor, 2004). The unique challenges, problems, stresses, and worries that children and families with mental health needs face are often read by counselors in a variety of settings (e.g., schools, community agencies, juvenile justice systems, child welfare programs, rehabilitation centers).…”
Section: Counselors and Children's Mental Healthmentioning
confidence: 99%
“…Counseling adults is different from counseling children due to unique challenges for the children's counselors that those who counsel adults do not experience (Van Velsor, 2004), and research have shown that a primary way to successfully counsel children is to acknowledge that children have unique and different cognitive levels and limited vocabulary (Van Velsor, 2004). One struggle that counselors face is children's ongoing developmental growth during their physical growth (Myers, Shoffner, & Briggs, 2002).…”
Section: Counseling Childrenmentioning
confidence: 99%
“…Thinking dialectically empowers older children and adults to recognize others' thoughts, views, and experiences as distinct and apart from theirs and to learn that they, too, are valid (Myers, 1998). When working with adults basic counseling skills such as verbal reflection and confirmation are enough, however, children communicate through actions and play, so the counselor must implement reflection through behavioral tracking (Van Velsor, 2004). Children often have not learned emotional regulation creating another challenge.…”
Section: Counseling Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Van Velsor (2004) describes microskills as the components used to develop a personal style in which feelings and meanings are reflected and interpreted toward the development of empathy and understanding. The microskills model, as adapted from Ivey et al’s (2007) original work by Blonna, Loschiavo, and Watter (2010), utilizes three groups of skills: attending, responding, and influencing, which are used together and are basic to all counseling frameworks (Figure 1 ).…”
Section: The Microskills Modelmentioning
confidence: 99%